If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -5x + 8 + 2x + 4x + -2 = 6 + 4 * 3 Reorder the terms: 5 + 8 + -2 + -5x + 2x + 4x = 6 + 4 * 3 Combine like terms: 5 + 8 = 13 13 + -2 + -5x + 2x + 4x = 6 + 4 * 3 Combine like terms: 13 + -2 = 11 11 + -5x + 2x + 4x = 6 + 4 * 3 Combine like terms: -5x + 2x = -3x 11 + -3x + 4x = 6 + 4 * 3 Combine like terms: -3x + 4x = 1x 11 + 1x = 6 + 4 * 3 Multiply 4 * 3 11 + 1x = 6 + 12 Combine like terms: 6 + 12 = 18 11 + 1x = 18 Solving 11 + 1x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 1x = 18 + -11 Combine like terms: 11 + -11 = 0 0 + 1x = 18 + -11 1x = 18 + -11 Combine like terms: 18 + -11 = 7 1x = 7 Divide each side by '1'. x = 7 Simplifying x = 7
| 1.12a=149000000 | | 7g+5=12g-25 | | 6p-(5p-5)=-8-2(p+12) | | 3x^4(7x^3-4x-1)= | | .25+9=10-.75r | | 5x(1-x)=5(x-2) | | 6x^2-7x-20=(2x-5)(3x+4) | | x(2x-3)=35 | | z^4+2z^2-4z=0 | | 8+4x-12-2x=8 | | (8a-7)(4a-3)=0 | | 3x^2+4x-5-7x^2-4x+8= | | 12(3x-9)=3(12x+5) | | In(x)=7 | | 42=6t | | 2x-8=x+7 | | Ln(4x-5)=0 | | 157.78=2.41w+14.23 | | -421=7(-4+7n)-1 | | Y=-3x-12+5 | | 12x+3=8x+7 | | -8p+9+9p=15 | | x^2+14x=900 | | 135+5=140-40 | | 0=x^2-14x+45 | | 5(2a-5b+3c)= | | d^2+12d+36= | | 7x-5=3x+10 | | -3-(-3x)=0 | | 3x+5=4x-40 | | -4-(-3x)=0 | | -2-(-3x)=0 |